Are perioperative interventions effective in preventing chronic pain after primary total knee replacement? A systematic review - Rachael Gooberman-Hill; Andrew David Beswick; Jane Dennis; Ashley William Blom; Vikki Wylde (BMJ Open)
Objectives For many people with advanced osteoarthritis, total knee replacement (TKR) is an effective treatment for relieving pain and improving function. Features of perioperative care may be associated with the adverse event of chronic pain 6 months or longer after surgery; effects may be direct, for example, through nerve damage or surgical complications, or indirect through adverse events. This systematic review aims to evaluate whether non-surgical perioperative interventions prevent long-term pain after TKR.Methods We conducted a systematic review of perioperative interventions for adults with osteoarthritis receiving primary TKR evaluated in a randomised controlled trial (RCT). We searched The Cochrane Library, MEDLINE, Embase, PsycINFO and CINAHL until February 2018. After screening, two reviewers evaluated articles. Studies at low risk of bias according to the Cochrane tool were included.Interventions Perioperative non-surgical interventions; control receiving no intervention or alternative treatment.Primary and secondary outcome measures Pain or score with pain component assessed at 6 months or longer postoperative.Results 44 RCTs at low risk of bias assessed long-term pain. Intervention heterogeneity precluded meta-analysis and definitive statements on effectiveness. Good-quality research provided generally weak evidence for small reductions in long-term pain with local infiltration analgesia (three studies), ketamine infusion (one study), pregabalin (one study) and supported early discharge (one study) compared with no intervention. For electric muscle stimulation (two studies), anabolic steroids (one study) and walking training (one study) there was a suggestion of more clinically important benefit. No concerns relating to long-term adverse events were reported. For a range of treatments there was no evidence linking them with unfavourable pain outcomes.Conclusions To prevent chronic pain after TKR, several perioperative interventions show benefits and merit further research. Good-quality studies assessing long-term pain after perioperative interventions are feasible and necessary to ensure that patients with osteoarthritis achieve good long-term outcomes after TKR.